Fitness profiles of elite adolescent Irish rugby union players - Wood, D. J.; Coughlan, G. F.; Delahunt, E. (The Journal of Strength and Conditioning Research, 2018)
Rugby unions throughout the world are implementing player development models to prepare young players to meet the demands of professional rugby union. An example of this is the Irish Rugby Football Union Long Term Player Development model. The purpose of this study was to provide normative data relating to the physical fitness of elite adolescent Irish rugby union players and determine the differences in the physical capacities between players in the forward and back units as well as to provide descriptive data for the position categorizations within these units for this unique population. Players in the forward unit were significantly taller and heavier than players in the back unit (1.85 ± 0.06 m and 96.88 ± 9.00 kg vs. 1.79 ± 0.05 m and 81.97 ± 7.09 kg, respectively). Forwards (38.37 ± 4.00 cm) had a significantly lower countermovement jump height than backs (41.31 ± 4.44 cm). Forwards had a significantly lower triple hop for the distance score on their right (5.78 ± 0.52 m) and left (5.78 ± 0.55 m) legs compared with backs (6.26 ± 0.42 m and 6.33 ± 0.45 m, respectively). Forwards (1.85 ± 0.07 seconds) had a significantly higher 10-m sprint time than backs (1.77 ± 0.06 seconds). Furthermore, forwards (675.90 ± 82.46 m) had a significantly lower 150-m shuttle test score than backs (711.71 ± 27.46 m). The results of this study provide normative data for players who currently possess underage international potential and could be used by strength and conditioning coaches to guide the selection of players through talent identification processes.